Mood, firm behavior, and aggregate economic outcomes - Chhaochharia, Vidhi; Kim, Dasol; Korniotis, George M.; Kumar, Alok (Journal of Financial Economics, 2019)
This study examines whether mood affects the aggregate state-level macroeconomy through its impact on firm-level decisions. Using sky cloud cover as a proxy for mood, we show that mood affects the economic expectations of small business managers. After relatively sunnier periods, managers have more optimistic expectations, and the component of their expectations related to mood influences hiring and investment decisions. Consequently, mood affects state-level job creation and new business starts, especially during periods of greater economic uncertainty. These results suggest that mood-induced economic expectations influence firm-level managerial decisions and state-level macroeconomic fluctuations.